The Effect of Implementing the Cooperative Integrated Reading and Composition (CIRC) Model with BUDI Media on Improving Reading Comprehension Skills Among Elementary School Students - Meilisa; Indah Nurmahanani; Nenden Permas Hikmatunisa (Lembaga Bale Literasi, 2026)
This study was motivated by students’ low reading comprehension skills, particularly in analyzing the deeper intrinsic elements of a story, as well as their reliance on learning resources that lack interactivity. This study aims to determine the effect of and improvement in students’ reading comprehension skills through the Cooperative Integrated Reading and Composition (CIRC) model supported by the BUDI media. This study uses a quantitative approach with a quasi-experimental design involving 40 fifth-grade students at an elementary school in Purwakarta Regency, with the experimental and control classes each consisting of 20 students. Data collection instruments consisted of an essay test and an observation sheet. The results showed that the Cooperative Integrated Reading and Composition (CIRC) model supported by BUDI significantly improved students’ reading comprehension, as evidenced by a higher post-test average score (90.25) for the experimental class compared to the control class (78.25). The contribution of the effect was 44.7%, and the increase in N-Gain was 69% for the experimental class compared to 33% for the control class. Thus, the Cooperative Integrated Reading and Composition (CIRC) model supported by the BUDI media proved to be more effective in improving the reading comprehension of elementary school students compared to the STAD model.